Development and application of fuel cells in the automobile industry. (October 2021) - Luo, Yang; Wu, Yinghong; Li, Bo; Mo, Tiande; Li, Yu; Feng, Shien-Ping; Qu, Jingkui; Chu, Paul K.
Highlights: Progress of fuel cell technologies in the automobile industry is summarized. Current status and marketing of fuel cell electric vehicles (FCEVs) are reviewed. Hydrogen FCEVs are technically feasible for the preliminary commercialization. Hybridization with a battery system will boost the dynamic response of FCEVs. Challenges for commercialization of FCEVs and future outlook are discussed. Abstract: The automotive industry consumes a large amount of fossil fuels consequently exacerbating the global environmental and energy crisis and fuel cell electric vehicles (FCEVs) are promising alternatives in the continuous transition to clean energy. This paper summarizes the recent development of fuel cell technologies from the perspectives of the automobile industry and discusses current bottlenecks hindering commercialization of FCEVs. Current status of the fuel cell technology, policies and market prospect of FCEVs, as well as recent progress of FCEVs are reviewed. Polymer electrolyte membrane fuel cells constitute the mainstream and most mature fuel cell technology for automobile applications. Hybridization with an auxiliary battery system will greatly boost the dynamic response of FCEVs. Hydrogen FCEVs have entered the preliminary commercialization stage since 2015 and the market share of FCEVs is expected to grow at a high rate. Challenges encountered by commercialization of FCEVs and future outlook are also discussed. Future efforts are expected to focus on solving problems such as the high cost of fuel cell stack production and maintenance, insufficient hydrogen supply facilities, insufficient reliability, slow cold start, safety concerns, and immature energy management systems of FCEVs. This review serves as a reference and guide for future technological development and commercialization of FCEVs. Graphical abstract: Image, graphical abstract